Antibacterial Activity of the Seeds of Hyoscyamus niger L. (Henbane) - Dulger, Basaran; S. Goncu, Beyza; Gucin, Fahrettin (Asian Journal of Chemistry, 2010)
The methanolic extract obtained from the seeds of Hyoscyamus niger L. (Solanaceae) was investigated for its antibacterial activity against Bacillus subtilis ATCC 6633, Bacillus cereus ATCC 7064, Staphylococcus aureus ATCC 6538P, Escherichia coli ATCC 10538, Proteus vulgaris ATCC 6899, Salmonella typhimurium CCM 5445 and Pseudomona s aeruginosa ATCC 27853 by disc diffusion and microdilution method. The extracts showed strong antibacterial activity against Staphylococcus aureus, with inhibition zones of 25.0 mm and with minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) of 16 (32) μg/mL, respectively. Also, the extracts exhibited moderate activity the other test bacteria. The results demonstrate that the methanolic extract of the seeds of H. niger has significant activity and suggest that it may be useful in the treatment of infections.